Efficacy and Safety of Supplemental Transarterial Chemoembolization Through Extrahepatic Collateral Arteries with Drug-eluting Beads: Treatment for Unresectable Hepatocellular Carcinoma - Chiu SH; Chang PY; Shih YL; Huang WY; Ko KH; Chang WC; Huang GS (Dove Medical Press, 2020)
Sung-Hua Chiu,1 Ping-Ying Chang,2 Yu-Lueng Shih,3 Wen-Yen Huang,4 Kai-Hsiung Ko,1 Wei-Chou Chang,1 Guo-Shu Huang1 1Department of Radiology, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 2Division of Hematology/Oncology, Department of Internal Medicine, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 3Division of Gastroenterology, Department of Internal Medicine, Tri-Service General Hospital, National Defense Medical Center, Taipei, Taiwan; 4Department of Radiotherapy, Tri-Service General Hospital, National Defense Medical Center, Taipei, TaiwanCorrespondence: Wei-Chou ChangDepartment of Radiology, Tri-Service General Hospital, National Defense Medical Center, Taipei, TaiwanTel +886-2- 8792-3311 ext. #16480Fax +886-2-8792-7245Email Weichou.chang@gmail.comPurpose: To evaluate the therapeutic efficacy and safety of supplement transarterial chemoembolization (TACE) with drug-eluting beads TACE (DEB-TACE) through extrahepatic collateral (EHC) arteries for the treatment of hepatocellular carcinoma (HCC).Patients and Methods: In this retrospective study, 61 unresectable HCC patients with treatment-naïve EHC blood supplies who received TACE from January 2016 to March 2019 were enrolled; of these patients, 42 (68.9%) received DEB-TACE, and 19 (31.1%) received cTACE. The hepatic tumor feeding arteries were treated in the same TACE session if it presented. The tumor response, time-to-progression (TTP), and overall survival (OS) were analyzed. Safety was assessed based on the occurrence of liver function deterioration and major complications within three months after TACE.Results: DEB-TACE showed better efficacy than cTACE in the disease control rate (p=0.001), overall response rate (p=0.005), the TTP (eight months vsthree months, p=0.002) and the OS (23.8 months vs nine months, p=0.045). Nine patients in the DEB-TACE group and one patient in the cTACE group were downstaged to resection or liver transplantation (21.4% vs 5.3%, p=0.151). DEB-TACE and cTACE have no difference in the acute and chronic liver toxicity. With regard to complications, there was no significant difference in the occurrence of both major (16.7% vs 21.1%, p=0.72) and minor (57.1% vs 47.4%, p=0.48) complications between DEB-TACE and cTACE.Conclusion: DEB-TACE through EHC arteries has a potential therapeutic effect in the treatment of unresectable HCC, with comparable safety compared with cTACE.Keywords: hepatocellular carcinoma, chemoembolization, therapeutic, collateral circulation, cone-beam computed tomography